Audit quality and real earnings management: evidence from the UK manufacturing sector. Issue 2 (5th November 2019) - Sitanggang, R.P.; Karbhari, Yusuf; Matemilola, Bolaji Tunde; Ariff, M.
Abstract : Purpose: The purpose of this paper is to investigate whether audit quality is associated with real earnings management in the UK. Design/methodology/approach: The authors apply the panel fixed effects method that controls for heterogeneity across firms to investigate whether audit quality is related to real earnings management for a large sample of UK manufacturing companies for the period 2010–2013. The authors utilized three proxies to measure real earnings management and two proxies to measure audit quality. Findings: The results provide evidence that audit fees are negatively related to abnormal operating cash flows. Conversely, audit fees are positively related to abnormal discretionary expenses. Besides, audit quality proxies show insignificant relationship with abnormal production costs and real earnings management index. Overall, the study finds partial evidence of significant relationship between audit quality and real earnings management. Research limitations/implications: These results are important subject to the adequacy of the indicators of real earnings management and audit quality. Like previous research works that mostly focus on upward earnings management, the authors do not address the question of whether and how firms take real actions to manage earnings downwards in certain contexts. Practical implications: The findings inform monitoring bodies that the imposition of higher levels of audit quality may result in unintended consequences. Therefore, monitoring bodies, such as audit committees, should consider the implication of imposing higher quality auditing, which may drive firms to potentially value-decreasing real earnings management practices. Managers should curtail real earnings management practices, especially abnormal operating cash flow, because attempt to use higher-quality auditors to mitigate such practice may destroy firm value. Also, managers' employment may be threatened due to the potential deterioration of firm value caused by using higher-quality auditors to mitigate managers' real earnings management practices. Moreover, shareholders are informed of the potential detrimental effects of imposing higher levels of audit quality which may lower the value of their investments. Originality/value: The paper extends previous research on earnings management in several ways. First, while earlier studies usually use accruals methods to measure earnings management, the authors use the real earnings management approach as managers can switch from accruals to real earnings management when facing more scrutiny from auditors and/or more constrained regulations or standards that may limit their capability to use discretionary accruals. Second, this study reports new findings, as the authors find partial evidence of a significant relationship between audit quality and real earnings management. Third, it is one of the few studies to use a real earnings management index to measure earnings management and its link to audit quality.